Solución estática axialmente simétrica de las ecuaciones de Einstein en coordenadas esferoidales generalizadas - Villegas S., Fulgencio (2002)
A general solution of the Einstein's equations in the vacuum and for a static and axial symmetric is obtained in terms of a coordinate system, which has as particular cases the prolates, oblates and spherical coordinates. The solution obtained is a generalization of the solutions corresponding to each of the three cases mentioned. © 2002 CSI. All rights reserved